The structure and optical properties of evaporated Samarium fluoride films - Su, Wei-tao; Li, Bin; Liu, Ding-quan; Zhang, Feng-shan (Applied surface science, 2008)
Samarium fluoride (SmF 3) films have been deposited on quartz, silicon and germanium substrates by vacuum evaporation method. The crystal structure of the films deposited on silicon substrate is examined by X-ray diffraction (XRD). The films deposited at 100 °C, 150 °C and 250 °C have the (1 1 1) preferred growth orientation, but the film deposited at 200 °C has (3 6 0) growth orientation. The surface morphology evolution of the films with different thickness is investigated with optical microscopy. It is shown that the microcrack density and orientation of thin film is different from that of thick film. The transmission spectrum of SmF 3 films is measured from 200 nm to 20 μm. It is found that this material has good transparency from deep violet to far infrared. The optical constants of SmF 3 films from 200 nm to 12 μm are calculated by fitting the transmission spectrum of the films using Lorentz oscillator model.